(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The family Carayonemidae (Hemiptera: Coccoidea) was established in 1986 for a neotropical species adapted to life in wet or aquatic habitats. So far, only four species belonging to the family, all neotropical, have been described. The phylogenetic affinities of the Carayonemidae, their specialised morphology and biology, and suitable collection methods are discussed.